A Viability Approach For Management Of IEEE 802.15.4 Wireless Sensor Node Performance - Karim Sidibe; Cheick Tidjane Kone; Tchimou N’Takpe; Boko Aka; Marí Soucase Bernabé (IAES Indonesian Section, 2021)
The long-term use of wireless sensors node while guaranteeing a good Quality of Services (QoS) is a major challenge in wireless sensor networks. Most of the relevant solutions which exist are proposed under Mac layer level but they use an optimization technique which requires a regular update of parameters and leads to unnecessary energy consumptiom which reduces the expected liftime and QoS. So in order to adress this issue, we propose in this paper, an adaptive management of wireless sensor node resources to meet application requirements in terms of energy consumption, reliability and delay. To do this, we have used the theory of viability, which is an approach that allows controling the evolution of a system in a set of desirable states. Here we have proposed an enhanced analytical model of sensor node’s energy dynamic, and we control it based on both Mac layer parameters of the IEEE 802.15.4 standard and the packet sampling frequency. The simulation results have shown that the proposed model is more accurate and efficient as a node can send more information without violating energy, reliability and delay constraints.